Sistem Informasi Monitoring Kinerja Sub-Agent Dalam Penjualan Tiket Pesawat Pada PT Fefva Tours & Travel - Muchollad, Azid Malil'ula Wildan; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: In the scope of ticket sales, PT Fefva Tours & Travel has many sub-agent who can not know the status of transaction. Currently active sub-agent only do the transactions depending on market conditions and the promo. In addition, there are also sub-agents that are non-active and not being able to sell the tickets. Under these conditions it will have an impact on the level of sales and profit levels of sales will decline so it does not meet the sales and profit targets have been determined. From these problems, it created an performance monitoring information system of sub-agent in the sale of airlines tickets. This system can count the ticket sales transaction as the basis for measuring the performance of a sub-agent in accordance with the predetermined targets during a specific time period. This system also requires a MBO method (Management By Objective) for an evaluation that focuses on how good the performance of the sub-agent. With this information system can help companies to produce monitoring reports sales and performance of profit earnings sub-agent based targets and a predetermined time period. In addition, it can be used as a performance evaluation process sub-agent in accordance with the objectives established by the company.